Moisture-dependent thermo-mechanical constitutive modeling of wood. Issue 1 (16th November 2018) - Fleischhauer, Robert; Hartig, Jens U.; Haller, Peer; Kaliske, Michael
Abstract : Purpose: The purpose of this study is the numerical investigation of densification and molding processes of wood. Providing theoretical and numerical approaches with respect to a consistent multi-physical finite element method framework are further goals of this research. Design/methodology/approach: Constitutive phenomenological descriptions of the thermo-mechanical and moisture-dependent material characteristics of wood are introduced. Special focus is given to a consistent hygro-thermo-mechanical modeling at finite deformations to capture the realistic material behavior of wood, especially when it is subjected to densification and molding processes. Findings: Realistic theoretical formulations of different hygro-thermo-mechanical processes are provided. A successful numerical modeling is demonstrated for beech wood by validation at experimental findings. Originality/value: The constitutive laws and numerical findings are new, as they govern a multi-physical large deformation framework and are applied to the advanced technology of densification and molding of wood.